Beautiful C++ 30 Core Guidelines for Writing Clean, Safe, and Fast Code - Gregory, Kate; Davidson, J. (Addison-Wesley Professional, 2021)
Conquer the Complexity of Modern C++ " Beautiful C++ presents the C++ Core Guidelines from a developer's point of view with an emphasis on what benefits can be obtained from following the rules and what nightmares can result from ignoring them. For true geeks, it is an easy and entertaining read. For most software developers, it offers something new and useful." --Bjarne Stroustrup, inventor of C++ and co-editor of the C++ Core Guidelines Writing great C++ code needn't be difficult. The C++ Core Guidelines can help every C++ developer design and write C++ programs that are exceptionally reliable, efficient, and well-performing. But the Guidelines are so jam-packed with excellent advice that it's hard to know where to start. Start here, with Beautiful C++ . Expert C++ programmers Guy Davidson and Kate Gregory identify 30 Core Guidelines you'll find especially valuable, and offer detailed practical knowledge for improving your C++ style. For easy reference, this book is structured to align closely with the official C++ Core Guidelines website. Throughout, Davidson and Gregory offer useful conceptual insights and expert sample code, illuminate proven ways to use both new and longstanding language features more successfully, and show how to write programs that are more robust and performant by default. Avoid "bikeshedding": stop wasting valuable time on trivia Don't hurt yourself by writing code that will cause problems later Know which legacy features to avoid and the modern features to use instead Use newer features properly, to get their benefits without creating new problems Default to higher-quality code that's statically type-safe, leak resistant, and easier to evolve Use the Core Guidelines with any modern version of C++: C++20, C++17, C++14 or C++11 Whether you've worked with C++ for decades or you've only recently focused on it, there's something here to improve virtually every program you write, design, or maintain.
Online resource; Title from title page (viewed December 23, 2021)
Keywords: C++ (Computer program language); Operating systems (Computers); C++ (Langage de programmation); Systèmes d'exploitation (Ordinateurs); operating systems